THE TECHNOLOGY OF BUCKWHEAT GROWING AS A PLANTING FILLER - Ivanyshyn, Volodymyr; Shuvar, Ivan; Havrylianchyk, Ruslan; Sendetskyi, Volodymyr; Bunchak, Olexandr; Tymofiichuk, Olexandr (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
Today it is a task to farmers to increase buckwheat production by expanding areas of buckwheat cultivation in intermediate crops because after cutting and stubble crops - an important reserve increase gross grain production efficiency and crop conditions for the agriculture sector intensification. Intermediate buckwheat crops have important economic and agronomic and economic importance. Obtaining two harvests a year from one field confirms the high intensity of management, thus increasingproductivity per hectare to 30-80%. The paper deals with the results of experimental and industrial studies on improving of the existing technologies of buckwheat cultivation for grain, green manure, green fodder during the intermediate sowing. The technological aspects of straw and after-reaping straw residues using for organic fertilizers by means of "Vermistim-D" destructor produced by PE "Bioconversion" (Ivano- Frankivsk) and new generation organic fertilizers " Biohumus", "Bìoproferm".